Electron Microscopic Analysis of Modified Foam Concrete (Eurasian Journal of Engineering and Technology, 2023)
The article presents the results of the physico-chemical analysis of the microstructure of foam concrete with the KDz-3ChMB complex chemical additive and the variable hydration and crystallization processes of cement stone using electron microscopic images. It was found that these additives in cement stone contribute to the emergence of new formations, crystallization in a thin dispersed medium, stitching of the capillaries and pores of Portland cement stone, densification and strengthening of its structure.